7. SURVEY ON THE CHARACTERISTICS OF DISEASE SYNDROMES IN TRADITIONAL MEDICINE FOR INTERNAL HEMORRHOID PATIENTS AT LE VAN THINH HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: Survey the prevalence of traditional medicine syndromes and characteristics of syndrome-specific symptoms in patients with internal hemorrhoids at Le Van Thinh Hospital.Subject and method: A cross-sectional descriptive study was conducted on 100 patients diagnosed with internal hemorrhoids according to inclusion criteria, who visited Le Van Thinh Hospital between January and April 2025.Results: Five traditional medicine disease syndromes were surveyed. Damp-heat pouring downward was the most prevalent (33%), followed by spleen qi sinking (26%), wind damaging intestinal collaterals (25%), qi stagnation and blood stasis (8%), and qi and blood deficiency (8%).Conclusion: Five traditional medicine disease syndromes were identified, with damp-heat pouring downward being the most common, followed by spleen qi sinking, wind damaging intestinal collaterals, and the less frequent patterns of qi stagnation and blood stasis and qi and blood deficiency
Keywords: Internal hemorrhoids, Goligher classification, traditional medicine syndromes.